2010
DOI: 10.5171/2010.552843
|View full text |Cite
|
Sign up to set email alerts
|

An Approach of Web Service Quality Attributes Specification

Abstract: Web Services are considered a new way of building software applications based on Services that are available through the Internet. However, Web Services still face many problems that are limiting their adoption. One of the causes of this problem is the lack of metadata about the quality attributes of Web Services, which make Service Requesters reluctant to integrate Web Service with their applications. This paper proposes a novel ontology that describes a model of the requester-oriented Web Services' quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The study has identified 41 distinctive measures of healthcare service quality (Table 2). The factors commonly used to measure the quality of servicescape are identified as physical environmental quality, diagnostic aspect of care, resources and capacity, tangibility, financial and physical access to care and access (Herstein & Gamliel, 2006; Ahmad & Sungip, 2008; Sharma & Narang, 2011; Simou, Pliatsika, Koutsogeorgou, & Roumeliotou, 2014; Marzban, Najafi, Etedal, Moradi, & Rajaee, 2015). Among the mentioned dimensions of servicescape, utilization has been less studied in the past.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study has identified 41 distinctive measures of healthcare service quality (Table 2). The factors commonly used to measure the quality of servicescape are identified as physical environmental quality, diagnostic aspect of care, resources and capacity, tangibility, financial and physical access to care and access (Herstein & Gamliel, 2006; Ahmad & Sungip, 2008; Sharma & Narang, 2011; Simou, Pliatsika, Koutsogeorgou, & Roumeliotou, 2014; Marzban, Najafi, Etedal, Moradi, & Rajaee, 2015). Among the mentioned dimensions of servicescape, utilization has been less studied in the past.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Descriptive statistics (29 articles) including mean and standard deviation has been the most frequently applied technique in healthcare service quality research followed by t -test (18 articles). It was also found that both techniques have been applied in combination because service quality can be obtained by ascertaining the difference between service perception and service expectation of patients using the SERVQUAL model (Ahmad & Sungip, 2008; Irfan & Ijaz, 2011; Zarei, Daneshkohan, Khabiri, & Arab, 2015; Torabipour, Sayaf, Salehi, & Ghasemzadeh, 2016). Other major techniques preferred by researchers include correlation (17 articles), regression (17 articles), systematic literature review (12 articles) and ANOVA (11 articles).…”
Section: Common Characteristics Of Reviewed Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…WSMO is presented as an ontology for semantically describing Semantic Web Services. Taking the Web Service Modeling Framework (WSMF) [35] as a starting point, WSMO refines and extends this framework, and develops a formal ontology and language. WSMF consists of four different main elements for describing semantic Web Services: (1) ontologies which provide the concepts and relationships used by other elements, (2) goals that define the users' objectives, i.e.…”
Section: Vi2 Domain Quality Modeling Using Standards and Ontologicalmentioning
confidence: 99%